Case study evaluation past, present and future challenges - Russell, Jill; Greenhalgh, Trisha; Kushner, Saville (Advances in program evaluation ;, 2015)
In todays world, with its preoccupation with impact assessments and results-based management, program evaluation is all too often framed as an affirmation of an official narrative rather than as a source of alternatives. The power of case study is its insistence on opening up rather than suppressing the complexity of social programs, on documenting multiple voices and exploring contested viewpoints. In this way, case study resists the trend towards evaluations that simply focus on what works, that reduce the complexity of social life to a single narrative, and to formulations that strip out most of what matters. Now more than ever, as government policies and programs orientate to global economic crisis and its impact on the lives of citizens and communities, we require evaluations that resist information loss and produce richness.